Food origin influences microbiota and stable isotope enrichment profiles of cold-adapted Collembola (Desoria ruseki) - Hao, Cao; de Jonge, Nadieh; Zhu, Dong; Feng, Lichao; Zhang, Bing; Chen, Ting-Wen; Wu, Donghui; Nielsen, Jeppe Lund (Frontiers in Microbiology, 2022)
Collembola are a group of globally distributed microarthropods that can tolerate low temperature and are active in extremely cold environments. While it is well known that animal diets can shape their microbiota, the microbiota of soil animals is not well-described, particularly for animals with limited food resources, such as Collembola active in winter at low temperatures. In this study, we explored the effects of three different food sources; corn litter (agriculture grain residuals), Mongolian oak litter (natural plant residuals), and yeast (common food for Collembola culture), on the microbiota of a winter-active Collembola species, Desoria ruseki. We found that microbial diversity and community composition of the Collembola were strongly altered after feeding with different food sources for 30 days. Collembola individuals fed on corn litter harbored the highest bacterial richness and were dominated by a representative of Microbacteriaceae. In contrast, those fed on yeast exhibited the lowest bacterial richness and were primarily colonized by Pseudomonas. The microbial communities associated with the winter-active Collembola differed significantly from those observed in the food. Collembola nutrient turnover also differed when cultured with different food sources, as indicated by the C and N stable isotopic signatures. Our study highlights microbial associations with stable isotopic enrichments of the host. Specifically, the Arthrobacter was positively correlated with δ13C enrichment in the host. Representatives of Microbacteriaceae, Micrococcaceae, TM7a, Devosia, and Rathayibacter were positively correlated with δ15N enrichment of the host. Our study indicates that food sources are major determinants for Collembola microbiota that simultaneously alter consumers' isotopic niches, thereby improving our understanding of the roles played by host-microbiota interactions in sustaining soil biodiversity during the winter.